'We are not barbarians': Gender politics and Turkey's quest for the West. (June 2015) - Bilgic, Ali
Turkey's policy-makers have historically aimed to position Turkey within the West by convincing the latter that Turkey meets the 'standards' of the West, that they 'are not barbarians'. This article aims to offer a gender analysis of Turkey's relations with the West by showing how 'devalorization' as feminization and hypermasculinization of the non-West becomes a source of insecurity for non-Western policy-makers. This gendered ontological insecurity is intensified when they face a military threat from a third party. The argument is that Turkey's policy-makers try to benefit from military crises in order to represent Turkey as a state meeting Western 'standards' of masculinity, and therefore to address its gendered 'devalorization'. The analysis aims to contribute to the literatures of postcolonial feminism and non-Western insecurities.